Pengaruh Akupresur Terhadap Penurunan Nyeri Dysmenorhea - Diyah Tepi Rahmawati; Ronalen Br Situmorang; Syami Yulianti (Poltekkes Kemenkes Surakarta, 2019)
Dysmenorrhea or menstrual pain is pain experienced by women of childbearing age due to the hormone prostaglandin which makes the uterus contract. Acupressure is known as one of the traditional Chinese therapeutic methods for healing dysmenorrhea by using finger massage techniques at the meridian points of certain body parts (acupuncture points). The purpose of this study was to determine the effect of acupressure in adolescent girls with complaints of menstrual pain or dysmenorrhoea. The method in this study is a quantitative bivariate with the type of research with the Quasy approach of pre-post one group design experiments, data analysis using T Pair test. Samples of 30 female teenagers were obtained by using purposive sampling technique. Research result. Empirically proven acupressure 100% can be an alternative non-pharmacological therapy that is able to overcome or minimize pain, a statistical test p value <0.001 which means that there is an effect of acupressure on decreasing dysmenorrhea pain in adolescent girls in the city of Bengkulu. With the use of the VAS (Visual Analaog Scale) in this study, the average pain reduction was 2.12. Suggestion. Acupressure is a therapy that is safe, easy, practical and needs to be applied independently and continuously to improve women's reproductive health. But further research is still needed for more valid and relevant results.